2008
DOI: 10.1111/j.1747-0765.2008.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

Silica availability in soils and river water in two watersheds on Java Island, Indonesia

Abstract: Silicon is a beneficial element for rice plants and is one of the major factors affecting the sustainability of rice production. We investigated silica (Si) availability and dynamics in soils of sawah, other land uses, and also in river and canal water in two watersheds in Citarum and Kaligarang, Java Island, Indonesia. The term sawah refers to a leveled and bounded rice field with an inlet and an outlet for irrigation and drainage, respectively. In the present study, we examined Si content in soils, plants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 18 publications
0
21
0
2
Order By: Relevance
“…Si is transported to stems and leaf blades and used to form silica body cells (Sato et al 1990). The formation of silica body cells depends on Si supply from soil and irrigation water (Husnain et al 2008). It is well known that deficiency of Si causes pathogenic disease like brown spot disease and blast (Datnoff et al 1997;Hayasaka et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Si is transported to stems and leaf blades and used to form silica body cells (Sato et al 1990). The formation of silica body cells depends on Si supply from soil and irrigation water (Husnain et al 2008). It is well known that deficiency of Si causes pathogenic disease like brown spot disease and blast (Datnoff et al 1997;Hayasaka et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Neal et al ( 2005 ) also reported that dissolved Si concentrations for waters were signifi cantly affected by temperature, pH and the type of crystalline Si with which equilibrium was established. Husnain et al ( 2008 ) reported that in Citarum River, Indonesia, the average Si concentration ranged from 22 to 37 mg SiO 2 L −1 in the upper stream and from 13 to 25 mg SiO 2 L −1 in the middle and lower streams, while in the Kaligarang River, the average Si concentration ranged from 34 to 54 mg SiO 2 L −1 in the upper stream and from 23 to 39 mg SiO 2 L −1 in the middle and lower streams, showing the difference was affected by the geological condition of the watersheds. Kawaguchi and Kyuma ( 1977 ) summarized that the average soluble Si concentrations in rivers on Java Island are 42.3, 30.2, 18.2 and 28.6 mg SiO 2 L −1 , respectively, with the geological substrate being volcanic ash, marl, lime and acid tuff loam.…”
Section: Silicon In Natural Watersmentioning
confidence: 97%
“…At pH 2-9, especially at physiological pH values, Si in soil is mainly present as monosilicic acid and conversion of monosilicic acid into ionic silicates is possible only at pH >9. The main factors infl uencing soil Si availability or Si-supplying power include types of soil and parent material, historical land-use change, soil pH, soil texture, soil Eh, organic matter, temperature and accompanying ions (Kawaguchi and Kyuma 1977 ;He and Li 1995 ;Cai et al 1997 ;Sumida 2002 ;Husnain et al 2008 ;Struyf et al 2010a , b ).…”
Section: Available Silicon In Soilsmentioning
confidence: 98%
See 1 more Smart Citation
“…Darmawan et al (2006) reported that over the past three decades, soil Si availability has decreased by 11-20%. Husnain et al (2008) reported that dissolved Si concentration in irrigation water in Indonesia has also decreased by 10-20% in the same period. Husnain et al (2011) stated that paddy soils contained available Si less than 300 mg SiO 2 kg -1 , a deficiency criterion proposed by Sumida (1992), in 76% out of total 92 paddy soils examined in West Sumatra, and 22.5% out of total 59 paddy soils in West Java, while in Central Java and East Java, it was less than 3% out of total 43 paddy soils in both provinces.…”
Section: Introductionmentioning
confidence: 99%